SOSIALISASI DAGUSIBU (DAPATKAN, GUNAKAN, SIMPAN, BUANG) OBAT DENGAN BENAR PADA IBU-IBU PKK DI DESA KEMINGKING DALAM KECAMATAN TAMAN RAJO PROVINSI JAMBI - Permatasari, Jelly; Wardani, Anggita Kresna; Etsa, Nadila Permata (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
DAGUSIBU (Get, Use, Save and Dispose of) is a socialization activity in the form of the process of planting habits or values and rules from one generation to another in the community on how to use and manage medicines that are good and right (DAGUSIBU MEDICINE). Improper use of drugs can cause side effects that will harm health. Before we use drugs, we should make sure that the medicines we take are following the indications. Physically, the dose is functional (does not change color, is homogeneous), and does not expire. So to protect the public from the dangers of using drugs that are not right and not appropriate for it, it is necessary to hold socialization about Dagusibu in applying it in daily life. The community usually gets medicine from the nearest health center when they are sick, or the community buys over-the-counter drugs at the nearest shops. This activity intends for PKK mothers in the village of Kemingking dalam, Taman Rajo Subdistrict, Jambi Province. The results of this DAGUSIBU socialization program are that the public knows more about medicines, from obtaining to being disposed of.